Luo Tong Formula Alleviates Diabetic Retinopathy in Rats Through Micro-200b Target - Bing Pang; Qing Ni; Sha Di; Li-juan Du; Ya-li Qin; Qing-wei Li; Min Li; Xiao-lin Tong (Frontiers Media S.A., 2020)
Aim: Diabetic retinopathy (DR) is a serious complication of diabetes (DM). Luo Tong formula (LTF) exerts protective effects against DR in rats, but its underlying mechanism remains unknown. Methods: Sprague-Dawley rats injected with streptozotocin (STZ) were used as an experimental diabetes model. LTF or calcium dobesilate (CaD) was administered to diabetic rats via gastric gavage. After the 12 weeks of treatment, blood and tissue samples were collected to determine serum glucose and retinal structure. Blood samples were collected for blood glucose and hemorheology analysis. Gene or protein expression levels were evaluated by immunohistochemistry, western blotting and/or quantitative real-time polymerase chain reaction (PCR). Results: DM rats exhibits significantly increased blood retinal-barrier (BRB) breakdown and VEGF/VEGFR expression in the retina, and decreased miR-200b and tight junction ZO-1/Occludin/ Claudin-5 genes expression, as well as Ang-1/Tie-2 expressions in the retina compared to normal control group. LTF treatment significantly moderated histological abnormalities in diabetic rats, independent of blood glucose level; improved some hemorrheological parameters; decreased the expressions of VEGF/VEGFR and BRB breakdown, significantly increased PEDF and tight junction proteins ZO-1/Occludin, as well as increased retinal miR-200b expression compared to non-treatment diabetic rats. Moreover, LTF prevented the reduction in Ang-1/Tie-2 expression. Conclusions: LTF treatment ameliorated DR through its repair vascular and attenuate vascular leakage. A mechanism involving miR-200b may contribute to benefit effects.